Visual reasoning analysis of female students in solving mathematical problems. (February 2020) - Darmadi, D; Sanusi, S
Abstract: To solve the problem of mathematics, students need reasoning. Visualizations can help in reasoning. This paper discusses the results of visual reasoning analysis of female students in solving mathematical problems. The method of study used is a qualitative method with the subject of female students of the Mathematics Education Study Program of Universitas PGRI Madiun. Data is validated with time triangulation. Data that is natural, deep, and widespread are displayed and analyzed. The conclusion of the study is: 1) to solve mathematical problems, female students perform complex steps of completing Polya, namely: understanding problems with visualizations, planning a problem solving with mathematics, planning a problem solving with elimination/substitution, implementing a plan to solve problems with elimination/substitution, checking results, planning to solve problems with determinations, implementing plans to solve the problems with determinations, examine results, plan to solve problems with coordinate points, implement plans to solve problems with coordinate points, check the results of the sponsorship with the coordinate points; 2) every activity in resolving the problem, female students have done reasoning. However, not all activities are identified to perform visual reasoning. Students tend to still focus on formalities; 3) in the issue, the subject performs reasoning deductive or inductive and visualizes contextually or mathematically as needed.